Assessment of Dysregulation of HERC6 and Essential Biological Processes in Response to Laser Therapy of Human Arm Skin - Safari, Saeed; Rostami-Nejad, Mohammad; Rezaei-Tavirani, Mostafa; Mansouri, Vahid; Razzaghi, Zahra; Rezaei-Tavirani, Majid (Journal of Lasers in Medical Sciences, 2020)
Introduction: The widespread application of lasers in medicine, especially in the treatment of diseases implies more investigations to understand the precious molecular mechanism of the laser effect on the human body. In the present study, the prominent role of HERC6 in response to CO2 Laser therapy of human skin is investigated. Methods: The numbers of 16 gene expression profiles before and after the treatment with the CO2 laser are downloaded from Gene Expression Omnibus (GEO), and differentially-expressed genes (DEGs) are analyzed to find the significant DEGs. Gene ontology analysis revealed that HERC6 and a set of its neighbors played a significant role in response to laser application. Results: The expression changes of 52 significant DEGs were compared via heat map analysis and 27 significant DEGs were introduced as the critical genes which are involved in response to laser irradiation. “Thymidylate kinase activity” among 9 clusters of biological terms was highlighted as an important biological process related to the identified DEGs. HERC2 was proposed as a critical DEG which was related to several essential cellular processes in response to laser application. Conclusion: The findings from the present study indicate that HERC6 and the numbers of its first neighbors are involved in the essential cellular response to laser therapy of human skin.